Talis Eras Cvm Lvstra Decem Tibi Volveret Aetas, Marselaer, Ingenio, Meritis, Et Stirpe Corvscvs. N. Burgund. Consil[iarius] - Dyck, Anton van (1678)
Flämischer Jurist und Staatsmann, Bürgermeister von Brüssel